METODE MATSAL DALAM ALQUR’AN - Syukri Syukri (SHAHIH (Jurnal Ilmu Kewahyuan), 2018)
“Mathematical teaching is widely used in the Qur'an in conveying the Divine messages to human beings to make it easier to understand and obey. The use of this method is more on the verses in the context of aqeedah, especially the creed of monotheism, the attributes and behavior of the unbelievers and the hypocrites, infaq treasures, the nature of the life of the world, and the image of life in the hereafter for both the inhabitants of heaven and the inhabitants of hell. Matsal is clear, which is directly indicated by the word matsal itself or a word with it, there is a hidden matsal and there is a loose matsal”